2013
DOI: 10.1016/j.neuropharm.2012.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Does interictal synchronization influence ictogenesis?

Abstract: The EEG recorded from epileptic patients presents with interictal discharges that are not associated with detectable clinical symptoms but are valuable for diagnostic purposes. Experimental studies have shown that interictal discharges and ictal events (i.e., seizures) are characterized intracellularly by similar (but for duration) neuronal depolarizations leading to sustained action potential firing, thus indicating that they may share similar cellular and pharmacological mechanisms. It has also been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…Activitydependent changes in excitability, pH, and gap-junction coupling should contribute to the ability of frequent interictal spiking to prevent the occurrence of seizures. In addition, in vitro evidence suggests that a main player in controlling ictogenesis might rest on the ability of recurring interictal spikes to decrease the transient elevations in extracellular potassium that, at least experimentally, appear to be instrumental for ictal discharge onset (Barbarosie et al 2002;Avoli et al 2013a).…”
Section: Interictal Events and Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Activitydependent changes in excitability, pH, and gap-junction coupling should contribute to the ability of frequent interictal spiking to prevent the occurrence of seizures. In addition, in vitro evidence suggests that a main player in controlling ictogenesis might rest on the ability of recurring interictal spikes to decrease the transient elevations in extracellular potassium that, at least experimentally, appear to be instrumental for ictal discharge onset (Barbarosie et al 2002;Avoli et al 2013a).…”
Section: Interictal Events and Seizuresmentioning
confidence: 99%
“…In the first part of this report, we will review the processes that presumably initiate, sustain, and terminate a partial seizure. In the second part, we will analyze the correlation between interictal events and ictal discharges (de Curtis and Avanzini 2001;de Curtis et al 2012;Avoli et al 2013a). …”
mentioning
confidence: 99%
“…Therefore, CA3-driven interictal events should insure that GABA release during the slow interictal discharge is down-regulated thus controlling the associated elevations in extracellular [K + ]. This hypothesis is further supported by experiments in which parahippocampal structures such as EC, amydala or insular cortex are stimulated at frequencies similar to those of CA3-driven interictal spikes (i.e., at 0.5-1.0 Hz) [21,67]. Clinical studies have indeed shown that low frequency stimulation -delivered through transcranial magnetic or deep-brain electrical procedures -can reduce seizures in epileptic patients not responding to conventional antiepileptic therapy [68][69][70][71].…”
Section: Interictal-ictal Interactionsmentioning
confidence: 84%
“…For instance, it has been shown that cutting the Schaffer collaterals in brain slices comprising interconnected hippocampus and entorhinal cortex networks during 4AP application, abolishes the propagation of CA3-driven interictal discharges to the entorhinal cortex and discloses slow interictal spikes and seizure-like events in this structure (asterisk and continuous line in (Fig. 5A), respectively) [21,66,67]. At the same time, however, ictal discharge is often preceded (and thus presumably initiated) by a slow interictal spike generated locally (double asterisks in Fig.…”
Section: Interictal-ictal Interactionsmentioning
confidence: 99%
See 1 more Smart Citation